The Practical Anarchist (American Philosophy, 2011)
The Practical Anarchist brings to light the work of Josiah Warren, eccentric American genius. Devoting his life to showing the practicality of an astonishing ideal, Warren devoted equal industry to the question of how to make a pair of shoes and how to remake the social world into an individualist paradise. This will be the first chance for many readers to encounter Warren’s writings, and in many cases their first publication since their original appearance in obscure, self-published periodicals, including The Peaceful Revolutionist (1833), the first American anarchist periodical. Moreover, they often appeared in a bizarre experimental typography. This volume presents, out of the welter of bewildering writings left by Warren, a reading text designed for today’ readers and students. It seeks to convey the practical value of many of Warren’s ideas, their continuing relevance.